Digestibility contributes to between-animal variation in feed efficiency in beef cows. (14th June 2019) - De La Torre, A.; Andueza, D.; Renand, G.; Baumont, R.; Cantalapiedra-Hijar, G.; Nozière, P.
Abstract : Residual feed intake (RFI ) is an alternative measure of feed efficiency (FE ) and is calculated as the difference between actual and expected feed intake. The biological mechanisms underlying animal-to-animal variation in FE are not well understood. The aim of this study was to investigate the digestive ability of beef cows selected for RFI divergence as heifers, using two contrasted diets. Fifteen 4-year-old beef cows were selected from a total of 69 heifers based on their RFI following the feedlot test. The selected heifers were ranked into high-RFI (+ 1.02 ± 0.28, n = 8) and low-RFI (−0.73 ± 0.28, n = 7), and a digestibility trial was performed after their first lactation. Both RFI groups were offered two different diets: 100% hay or a fattening diet which consisted of a DM basis of 67% whole-plant maize silage and 33% high starch concentrates over four experimental periods (two per diet). A diet effect was observed on feed intake and apparent digestibility, whereas no diet × RFI interaction was detected ( P > 0.05). Intake and apparent digestibility were higher in cows fed the fattening diet than in those fed the hay diet ( P < 0.0001). DM intake (DMI ) and organic matter apparent digestibility (OMd ) were repeatable and positively correlated between the two subsequent periods of measurements. For the hay and fattening diets, the repeatability between periods was r = 0.71 and r = 0.73 for DMI and r = 0.87 and r = 0.48 for OMd, respectively. Moreover, both intake ( r = 0.55) and OMd ( r = 0.54) were positively correlated ( P < 0.05) between the hay and fattening diets. Significant differences between beef cows selected for divergence in RFI as heifers were observed for digestive traits ( P < 0.05), DM and organic matter (OM ) apparent digestibility being higher for low-RFI cows. Overall, this study showed that apparent digestibility contributes to between-animal variation in FE in beef cows.